The effect of electrical stimulation on sports rehabilitation in elderly people in nursing homes - Hussein, L. Dr. Anas Saadoun (Sulaimani Journal for Humanities, 2026)
The importance of the study is to improve muscle strength. And increase muscle mass. “, improves the range of movement of joints. Reduce pain and inflammation. Accelerate the healing process of injuries. And improve balance and walking ability. The researcher used the descriptive method to describe the effect of electrical stimulation on physical functions in a sample of older persons. The selection criteria at the Babylon Elderly Home were selected randomly and number (50), and the conclusions were: there is a strong correlation between electrical stimulation and the rehabilitation of elderly injuries. Studies have shown that electrical stimulation can be effective in improving: muscle strength molar mass job range balancing and walking ability. The sports rehabilitation program should include a combination of electrical stimulation and exercise. Individual design for everyone. Recommendations: Further studies should be undertaken to determine the optimal protocol for the use of electrical stimulation in the rehabilitation of older persons’ injuries. Sports rehabilitation programs for older people should include a combination of electrical stimulation and exercise. Sports rehabilitation programs should be designed individually for each person
Keywords: Electrical stimulation Sports qualification